Some Normal Criteria about Shared Values with Their Multiplicity Zeros - Jianming Qi; Taiying Zhu (Abstract and Applied Analysis)
Let F be a family of meromorphic functions in the domain D, all of whose zeros are multiple. Let n  (n≥2) be an integer and let a, b be two nonzero finite complex numbers. If f+a(f')n and g+a(g')n share b in D for every pair of functions f,g∈F, then F is normal in D.